Codeswitching and discourse markers in the narratives of a bilingual speaker with aphasia. Issue 2 (1st February 2017) - Neumann, Yael; Walters, Joel; Altman, Carmit
ABSTRACT: Background : Codeswitching and discourse markers are proposed as potentially compensatory means to promote fluency in bilingual people diagnosed with nonfluent aphasia. Aim : This paper examined four linguistic markers of aphasia and fluency—grammaticality, complexity, codeswitching, and discourse markers—in the narratives of a bilingual speaker, in order to assess whether and to what extent these phenomena are manifested in the two languages of a person with aphasia. Methods & Procedures : Sixteen narratives per language were collected, using a cue word procedure, from a 59-year-old Yiddish–English bilingual with diagnosed moderate nonfluent aphasia. Analyses of frequency and locus of ungrammaticality, sentence complexity, codeswitching, and discourse markers were conducted as well as motivations for codeswitching. Outcomes & Results : Findings showed more ungrammaticality in English (L2) than Yiddish (L1), relatively similar levels of complexity, and very similar use of discourse markers in both languages. Codeswitching was more prevalent in Yiddish (L1), motivated by lexical access difficulties, whereas in English (L2), codeswitching was motivated both by lexical access and cross-linguistic lexicalization differences. Conclusions : Differential use of codeswitching across the languages of a bilingual person with nonfluent aphasia shows that different strategies are used to enhance fluency and compensate for ungrammaticality in each language. Clinically, the study shows the importance of assessment in both languages, and suggests that intervention in both languages should be considered pending further investigation.